Early detection of Knudson's two-hits in preneoplastic renal cells of the Eker rat model by the laser microdissection procedure - Kubo, Yoshiaki; Klimek, Fritz; Kikuchi, Yasushi; Bannasch, Peter; Hino, Okio (Cancer research, 1995)
Hereditary renal cell carcinomas invariably develop by the age of 1 year in Eker rats. At the histological level, renal cell carcinomas develop through multiple stages from early preneoplastic lesions (e.g., phenotypically altered tubules) to adenomas. We previously reported that ionizing radiation induces additional tumors (large adenomas and carcinomas) in a linear dose-response relationship and that loss of heterozygosity (LOH) at chromosome 10, where the predisposing tuberous sclerosis (Tsc2) gene is localized, was found in the renal cell carcinomas which developed from hybrid F1 rats carrying the Eker mutation, indicating that in heterozygotes two events (one inherited, one somatic) are necessary to produce at least large adenomas and carcinomas. This study was designed to examine LOH in the earliest preneoplastic lesions, using a laser microdissection procedure. We could accurately dissect single altered renal tubules out of freeze-dried sections and clearly detected LOH in 4 of 19 altered tubules (21%). This is the first demonstration of LOH in single renal tubules. Our present results support the theory of a second, somatic mutation (second hit) as rate-limiting step of renal carcinogenesis in the Eker rat model of dominantly inherited cancer and the tumor suppressor nature of the Tsc2 gene function.
Gesehen am 11.12.2023